(untitled) (Journal of Education and Development, 2019)
Background: Over the years, mathematics and sciences have been performed poorly worldwide. There is an overwhelming high failure rates of mathematics and sciences in the marginalized schools found in Nakivale refugee settlement in Uganda. Electronic (e)-learning tools could be promising interactive strategies for teaching mathematics and sciences. There is lack of studies documenting educational challenges in the refugee settlement, and how e-learning can address the challenges. Objective: To identify the challenges experienced in teaching and learning mathematics and sciences in schools found in Nakivale refugee settlement, and explore the potentials of using e-learning to address the identified challenges. Methods: We employed a parallel mixed methods study design that utilized focus group discussions and surveys. We purposively conducted a focus group discussion with the 17 mathematics/science teachers that we had trained (in e-learning) from 6 schools in Nakivale refugee settlement. We also administered surveys to 267 learners and mathematics/science teachers of the six participating schools. Results: Educational challenges reported by participants are: 1) lack of access to modern teaching and learning resources, 2) Leaners’ negative attitudes towards mathematics and science, 3) overwhelming number of learners in class. 4) Lack of ICT pedagogical skills. They anticipated that e-learning could potentially: 1) enable unlimited and flexible access to educational resources, and 2) enhance engagement, interest and understanding of learning concepts. They however worried about the availability of sufficient technological infrastructure (e.g. internet, computers, and electricity) and skills to use the application. Conclusion: E-learning may enable unlimited and flexible access to educational resources, and enhance engagement, interest and understanding of learning concepts, which could potentially improve performance in mathematics and sciences in otherwise marginalized schools.